Zoledronate for patients with invasive residual disease after anthracyclines-taxane-based chemotherapy for early breast cancer – The Phase III NeoAdjuvant Trial Add-oN (NaTaN) study (GBG 36/ABCSG 29). (September 2016) - von Minckwitz, G.; Rezai, M.; Tesch, H.; Huober, J.; Gerber, B.; Zahm, D.M.; Hilfrich, J.; Costa, S.D.; Dubsky, P.; Blohmer, J.U.; Denkert, C.; Hanusch, C.; et al.
Abstract: Background: Patients with invasive residual disease after neoadjuvant chemotherapy (NACT) are considered to have chemo-resistant breast cancer. Bisphosphonates are an established treatment for bone metastases and are of potential benefit as adjuvant treatment in early breast cancer. Patients and methods: Patients who had invasive tumour residuals (ypT1-4 and/or ypN+) after a minimum of four cycles of anthracycline-taxane-containing NACT were eligible for the NeoAdjuvant Trial Add-oN study. Patients were randomised within 3 years after surgery to receive zoledronate 4 mg i.v. for 5 years versus observation. Zoledronate was given every 4 weeks for the first 6 months, every 3 months for the following 2 years, and every 6 months for the last 2.5 years. Primary objective was disease-free survival. Results: After a median time of 54.7 months no difference in disease-free survival was observed between the zoledronate and observation groups (hazard ratio [HR] 0.960, 95% confidence interval [CI] 0.709–1.30, log rank P  = 0.789). Various subgroups were examined without identifying a treatment effect of zoledronate. Patients over 55 years of age showed a HR of 0.832 in favour of zoledronate, but the result was not significant ( P  = 0.480). A similar result was obtained for overall survival with a HR of 1.19 (95% CI 0.79–1.79; log rank P  = 0.408). Zoledronate was well tolerated and no new toxicity signal was identified. Conclusion: Postneoadjuvant treatment with zoledronate does not improve outcome in patients without pathological complete response after neoadjuvant anthracycline-taxane-based chemotherapy for early breast cancer. Highlights: Tumours of patients with residual disease after neoadjuvant chemotherapy are considered chemo-resistant. Postneoadjuvant zoledronate did not improve outcome in non-pathological complete response patients. No subgroup benefitted significantly from this treatment. Postneoadjuvant zoledronate should not be routinely used in early breast cancer.